2000
DOI: 10.1152/ajpcell.2000.278.5.c965
|View full text |Cite
|
Sign up to set email alerts
|

Probing the extracellular release site of the plasma membrane calcium pump

Abstract: The plasma membrane Ca(2+) pump is known to mediate Ca(2+)/H(+) exchange. Extracellular protons activated (45)Ca(2+) efflux from human red blood cells with a half-maximal inhibition constant of 2 nM when the intracellular pH was fixed. An increase in pH from 7.2 to 8.2 decreased the IC(50) for extracellular Ca(2+) from approximately 33 to approximately 6 mM. Changing the membrane potential by >54 mV had no effect on the IC(50) for extracellular Ca(2+). This argues against Ca(2+) release through a high-field ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…Because the PMCA exports one cytosolic Ca 2ϩ in exchange for one or two extracellular protons, lowering the proton concentration in the bath slows pumping (18). We found that raising the pH in the bath solution to 8.8 (Na8.8) slowed especially the late phase of Ca 2ϩ clearance (Fig.…”
Section: Delayed Release Of Camentioning
confidence: 70%
See 2 more Smart Citations
“…Because the PMCA exports one cytosolic Ca 2ϩ in exchange for one or two extracellular protons, lowering the proton concentration in the bath slows pumping (18). We found that raising the pH in the bath solution to 8.8 (Na8.8) slowed especially the late phase of Ca 2ϩ clearance (Fig.…”
Section: Delayed Release Of Camentioning
confidence: 70%
“…with half-saturating concentration (K PMCA ) of 0.50 mol/l (28) multiplied by a titration function expressing the activation of pumping by protons with a pKa of 7.86 (18). Bidirectional transport by the NCX is computed according to a complex rate equation derived from experiments on electrogenic transport in cardiac myocytes (28).…”
Section: Relative Contributions To Camentioning
confidence: 99%
See 1 more Smart Citation
“…PMCA exchanges extracellular proton(s) for intracellular Ca 2ϩ (Niggli et al 1982;Smallwood et al 1983;Xu and Roufogalis 1988), and it can be inhibited by raising the external pH (Kratje et al 1985;Xu et al 2000). Instead of single APs we used trains of APs since [Ca 2ϩ ] i decayed more slowly after a train of APs and thus it was easier to measure.…”
Section: Plasma Membrane Ca 2ϩ Atpase Is Important For Clearance Of Pmentioning
confidence: 99%
“…Studies of erythrocytes have shown that the PMCA exchanges extracellular proton(s) for intracellular Ca 2ϩ (Niggli et al, 1982;Smallwood et al, 1983;Xu and Roufogalis, 1988), and it can be inhibited by raising the external pH (Kratje et al, 1985;Xu et al, 2000). High pH (8.8) has been used to inhibit the PMCA in squid axons (Dipolo and Beauge, 1982), rat sensory neurons (Benham The boutons were ordered from distal to proximal, with the most distal bouton along a branch assigned number 1.…”
Section: The Effect Of Bouton Position On Ca 2؉ Influxmentioning
confidence: 99%